2006
DOI: 10.1111/j.1365-2648.2006.03943.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of maternal sensitivity during the early postpartum period

Abstract: Providing social support, enhancing maternal identity, and facilitating maternal-fetal attachment in the antepartum period are recommended to improve postpartum maternal sensitivity. Also, in future research, a path-type model or structural equation model including other variables, such as postnatal depression, needs to be developed and tested for optimal adaptation to becoming a mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 43 publications
3
98
1
9
Order By: Relevance
“…Entre as variáveis que positivamente influenciam na intensidade do AMF, está o avanço da idade gestacional, a presença dos movimentos fetais, a história da gravidez e a história de apego da própria mãe (Lerum, Major, & LoBiondoWood, 1989;Honjo e cols., 2003;Righetti, Dell`Avanzo, Grigio, & Nicolini, 2005), o apoio social dos membros da família e pares (Cranley, 1984;Shin, Park, & Kim, 2006) e o planejamento da gravidez (Shieh, Kravitz, & Wang, 2001;Salisbury, Law, LaGasse, & Lester, 2003).…”
unclassified
“…Entre as variáveis que positivamente influenciam na intensidade do AMF, está o avanço da idade gestacional, a presença dos movimentos fetais, a história da gravidez e a história de apego da própria mãe (Lerum, Major, & LoBiondoWood, 1989;Honjo e cols., 2003;Righetti, Dell`Avanzo, Grigio, & Nicolini, 2005), o apoio social dos membros da família e pares (Cranley, 1984;Shin, Park, & Kim, 2006) e o planejamento da gravidez (Shieh, Kravitz, & Wang, 2001;Salisbury, Law, LaGasse, & Lester, 2003).…”
unclassified
“…The literature review already demonstrated a relation between these variables, revealing that maternal-fetal attachment was the variable with the highest predictive power (31%) of sensitivity when compared to social support, maternal identification and socio-demographic variables (Shin et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
“…Other maternity-related variables have been investigated as predictors of sensitivity, which were shown to influence that factor, including the mother's personality (Prinzie, Stams, Dekovic, Reijntjes, & Belsky, 2009), social support and the relation with the child's father (Piccinini, Marin, Alvarenga, Lopes, & Tudge, 2007;Shin et al, 2006), self-esteem (Shin, Park, Ryu, & Seomun, 2008) and identification with the infant (Shin et al, 2008). Finally, it is important to highlight that infant-related variables like irritability or negative affect (Mills-Koonce et al, 2007) for example, or even the child's gender (Thun-Hohenstein et al, 2008), can also influence maternal sensitivity and should be investigated, but go beyond the scope of the present study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the women diagnosed with HIV during pregnancy most likely lack the knowledge of HIV disease and the experience in coping with this disease, in addition to providing this information, they may benefit from working on issues related to maternal-fetal attachment, marital relationship, and planned pregnancy status to improve their health behaviors during pregnancy. The maternal sensitivity and reflective functioning that equips a mother to effectively read and respond to the cues of her infant could be extended downward to the prenatal period by facilitating maternal-fetal attachments (Shin, Park, & Kim, 2006;Slade, Sadle, & Mayes, 2005).…”
Section: Practicementioning
confidence: 99%